Evaluation Criteria of Facilities Management Through Public-Private Partnership (PPP) Scheme - Samsudin, Nurul Aqilah; Hashim, Hariati Abdullah; Hamzah, Ezdihar; Zainol, Nurul Nadiah (International Journal of Sustainable Construction Engineering and Technology, 2022)
The delivery of facilities management (FM) services through the Public-Private Partnership scheme has been increasing in recent years. The long-term success of this partnership depends mainly on the choice of the best-suited private partner. However, an issue regarding the unavailability of evaluation criteria was discovered when selecting the best FM service providers within this scheme. Preliminary research shows that evaluation criteria are the fundamental elements of the FM procurement process, yet little attention is given to this subject. The evaluation criteria are fundamental in choosing the most qualified FM service providers, especially in a complex project like PPP. Thus, this research aims to identify the evaluation criteria for FM through the PPP scheme. An in-depth literature review was conducted in this paper. The focus of the review was associated with the evaluation criteria of FM service providers in the PPP scheme. This paper identified four criteria that should be considered, namely clients’ requirements, external environment/factors, project characteristics, and financial advantages. The outcome of this paper can be used as a theoretical basis for the development of the FM procurement framework for the PPP scheme.